Genetic and Physical Interactions Involving the Yeast Nuclear Cap-Binding Complex - Fortes, Puri (American Society for Microbiology, 1999)
Yeast strains lacking the yeast nuclear cap-binding complex (yCBC) are viable, although impaired in growth. We have taken advantage of this observation to carry out a genetic screen for components that show synthetic lethality (SL) with a cbp20-Δ cbp80-Δ double mutation. One set of SL interactions was due to mutations that were complemented by components of U1 small nuclear RNP (snRNP) and the yeast splicing commitment complex. These interactions confirm the role of yCBC in commitment complex formation. Physical interaction of yCBC with the commitment complex components Mud10p and Mud2p, which may directly mediate yCBC function, was demonstrated. Unexpectedly, we identified multiple SL mutations that were complemented by Cbf5p and Nop58p. These are components of the two major classes of yeast small nucleolar RNPs, which function in the maturation of rRNA precursors. Mutants lacking yCBC were found to be defective in rRNA processing. Analysis of the yCBC deletion phenotype suggests that this is likely to be due to a defect in the splicing of a subset of ribosomal protein mRNA precursors.